INTEGRASI KEARIFAN LOKAL DALAM PEMBELAJARAN DI SD NEGERI 1 KRASAK - Adhela Falaby Rahman; Anisa Triyani; Asyifa Nur Khofifah; Nova Nur Ramandhani; Nugroho Prasetya Adi (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2025)
This study aims to describe teachers' understanding and implementation of local wisdom-based learning at SDN 1 Krasak, Wonosobo. The local wisdom in question includes traditions and cultural values ​​such as ruwatan rambut gimbal, topo bisu, and merdi desa. Through observation and interview methods, it is known that teachers have a fairly good understanding of local wisdom and show efforts to integrate it into learning, especially through the Pancasila Student Profile Strengthening Project (P5). However, this integration has not been carried out systematically because there are no teaching modules and learning guidelines that directly support it. In addition to the limitations of teaching tools, other challenges include the lack of teacher training, time constraints in the curriculum, and minimal cross-party collaboration. Local wisdom-based learning is currently more incidental and has not become part of the core curriculum. Therefore, it is necessary to develop a contextual curriculum, teacher training, and more affirmative education policies to make local cultural values ​​an important part of students' character education. Learning that is rooted in local culture is believed to be able to strengthen identity, foster a love for one's own culture, and form a generation with character.